Safety Timeout for Local Anesthetics and Regional Anesthesia - Sinardja, Cynthia Dewi; Widnyana, I Made Gde; Lolobali, Marilaeta Cindryani (Bali Journal of Anesthesiology, 2017)
Our anesthesia practices are always based on patient safety in WHO surgical and anesthesia guidelines. Those guidelines are interpreted in checklists and protocols that could be applied in daily routine in every standard operating theaters. A surgical patient would be notified and identified during the surgery by all member of the operating room including the anesthesiologist through a specialized checklists which was called a safety surgical checklist usually done in the preparation room, signing in, 5 minutes for timeout before the incision, and the last sign out before closure stitching. Anesthesia conduct and monitoring is viewed as a part of the whole surgery practice.The safety timeout that has been elaborated in ASRA Regional Block Pre-Procedural Checklist is one important thing that needs to be encouraged and confirmed every time an anesthesiologist is getting ready to do a regional anesthesia. Â The safety timeout is useful as a quick reminder for operating theater personnel especially anesthesiologist and the nurse anesthetists to do a double check and reassessment on patient condition, drug and adjuvant choice, labels, and other implicating factors. There are many contributing factors that could induced emergency and crisis situations in regional anesthesia conduct, and the safety timeout is an alternative way to eliminate and trace those factors in an appropriate way.